Utilization of three levels of pepper juice at 0.2, 0.4 and 0.6% as antioxidant and two types of tripa (natural and collagen) to be bound in the preparation of fresh chorizo - Ricaurte Ortiz, Paul (2017)
At present there is an indiscriminate use in the meat industry of synthetic additives before which the present research proposes the use of pepper juice as an antioxidant and two types of gut; a completely randomized design was applied with 8 treatments and 3 replicates. The results of the physical chemical analysis determined that the best results were obtained in relation to the moisture, protein and fat contents when T3 (0.6%) of pepper juice was used and incorporated into synthetic gut. The organoleptic tests were performed with randomly chosen judges, who rated the samples on a total of 20 points, of which the best score obtained T3 (0.6%) with a score of 17.86 points, and the synthetic gut obtained 17.32 points On the natural one with 16.21 points. Microbiological tests have values within the parameters allowed by the norm INEN 1344-96, which determines that the product is suitable for human consumption. The cost of production of chorizo is increased with the use of synthetic casing since a lower cost benefit was obtained (1.15).